Q: If 3y equals 12 then 2y equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

For y - 2y - 3y equals 0, y equals 0.

2x-3y=5 and x-2y=12x-3y+2y=5 and x-2y+2y=12x-y=5 and x=12(1)-y=52-y=52-y-2=5-2-y=3y=-3(x,y) is (1,-3)

9y-3y=6y; 6y+2y=8y; so your answer is 8y

2y+3y-7y+4=16 -2y=12y=-6Check it-12-18+42+4=16-30+46=1616=16

5 - 2y = 3y - 5 10 = 5y So, y = 2.

Related questions

If 3y = 12, 2y = 8

5y = 3y + 12 5y - 3y = (3y - 3y) + 12 2y = 12 y = 6

x = 3y - 3 so 6 (3y - 3) + 2y = -12 ie 18y - 18 + 2y = -12 ie 20y = 6 so y = 0.3 and x = -2.1

For y - 2y - 3y equals 0, y equals 0.

5y-2y= 3y+2 5y-2y-3y= 2 0y= 2

5 - 2y = -3y - 2Subtract 5 from each side:-2y = -3y - 7Add 3y to each side:y = -7

3y - 3 = 2y + 5 3y - 2y = 5 + 3 y = 8

perpendicular

2x-3y=5 and x-2y=12x-3y+2y=5 and x-2y+2y=12x-y=5 and x=12(1)-y=52-y=52-y-2=5-2-y=3y=-3(x,y) is (1,-3)

9y-3y=6y; 6y+2y=8y; so your answer is 8y

2y + 3 = 3y + 9 2y - 3y = 9 - 3 or -y = 6 so y = -6

2y+3y-7y+4=16 -2y=12y=-6Check it-12-18+42+4=16-30+46=1616=16